2007
DOI: 10.1007/s11099-007-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and yield responses of ozone-polluted winter wheat to drought

Abstract: Winter wheat (Triticum aestivum L. cv. Jingdong 8) was exposed to short-term high ozone treatment after anthesis and then was either well irrigated with soil water content (SWC) of 80-85 % (O 3 +W) or drought treated (SWC 35-40 %, O 3 +D). Short-term ozone exposure significantly decreased irradiance-saturated net photosynthetic rate (P N ) of winter wheat. Under good SWC, P N of the O 3 -treated plant was similar to that of control on 2 d after O 3 -exposure (6 DAA), but decreased significantly after 13 DAA, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The production of reactive oxygen species (ROS) is the important cause of damage to plants when exposed to environmental stress, which resulted in the growth inhibition, the breakdown of lipid membrane, and oxidative stress [20,23,24]. Liang et al [1] reported that cold damage significantly increased oxidative stress in wheat seedlings, and Liu et al Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The production of reactive oxygen species (ROS) is the important cause of damage to plants when exposed to environmental stress, which resulted in the growth inhibition, the breakdown of lipid membrane, and oxidative stress [20,23,24]. Liang et al [1] reported that cold damage significantly increased oxidative stress in wheat seedlings, and Liu et al Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tropospheric O 3 is a health hazard for us. It attacks all plant species and decreases their photosynthesis and growth rates, concomitantly with whitedot symptoms on the leaves of herbaceous species and reddish-to-black-dot symptoms on the leaves of arboreous, leguminous, and gramineous species (Hill and Littlefield 1969, Nouchi 2001, Izuta 2003, Xu et al 2007) and, in the cell, it also damages organelles and biopolymers, including DNA (Roshchina and Roshchina 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, short-term high O 3 exposure (125 mm 3 m -3 , 7 h d -1 for 4 d) to potted winter wheat after anthesis resulted in yield reduction by 21 % (Xu et al 2007). Besides reduced P N in damaged flag leaves, O 3 -treated plants showed premature leaf senescence 5 d earlier than control, which indicated that grain-filling duration was shortened.…”
Section: Discussionmentioning
confidence: 87%